«Une seule personne, une seule hypostase»: Origine et sens de la formule de Chalcédoine - Galot, Jean (Gregorianum, 1989)
The origin of the Chalcedonian formula "one person only, one hypostasis" must be found in the formula of Flavian, not simply in an expression used by Cyril of Alexandria, which though similar is not identical. The formula of Flavian itself is derived from the doctrine professed by Proclus, his predecessor. It is this doctrine which the article studies more deeply. Proclus has developed a christology of the one hypostasis in two natures, based on his interpretation of the Gospel data. He understood correctly that the miracles worked by Jesus and the powers exercised by him, for instance that of remitting sins, show that he is God, that he possesses the divine nature, distinct from the human, and that, consequently, he is one hypostasis in two natures. His doctrine is not without imperfections, for he divides too easily the actions of the earthly Christ, attributing some to the human nature and others to the divine, while in fact all the visible actions are human actions of the divine hypostasis. However, he has the great merit of being the first to have defined Christ clearly as "one single complete hypostasis in two complete natures". He thus inaugurated the current of thought which later would find expression at Chalcedon.